Profesionalismus a amatérismus v zrcadle socialistického sportu [Professionalism and amateurism in the mirror of the socialistic sport] - Brigita Stloukalová (Palacký University Olomouc, 2008)
Po 2. světové válce se sport ocitl v nových společenských poměrech, určených existencí dvou světových hospodářských soustav. Dlouholetý předseda Mezinárodního olympijského výboru (dále MOV) Avery Brundage odolal tlaku mezinárodních sportovních federací i národních olympijských výborů na vyplácení tréninkových a cestovních nákladů, jeho následovník lord Michael Killanin už uzdu povolil. Stavidla s definitivní platností otevřel ambiciózní Juan Antonio Samaranch, který se stal neomezeným diktátorem olympijského hnutí v 80. a 90. letech 20. století. Právě on umožnil vyplácení vysokých finančních částek sportovcům, a tím i účast profesionálních sportovců na olympijských hrách. Jaký vlastně byl vztah tzv. amatérského a profesionálního sportu? Byli sportovci v socialistických zemích amatéři nebo profesionálové? Jak socialistické země akceptovaly změny v olympijském hnutí v osmdesátých letech minulého století? Na tyto otázky se snaží předložený text odpovědět, přičemž hlavním zdrojem informací jsou soudobé dokumenty a denní tisk. [Professional and amateur sport formed as picture of society lay-out in modern history. The first amateur definitions considered as the professional everybody who had exercised manual labour. VIII. Olympic Congress in Prague in 1925 established the professional practised a sport for money or received a refund of wages. This definition had survived in almost unchanged form as late as the second half of the 20th century, when sport stepped foot inside new social conditions determined with two world economic systems existence. The VIII. Olympic congress in Prague in 1925 established nobody could participate in the Olympic Games: 1) who was professional or had been professional wittingly in his sport or other one, 2) who received refund of wages. This definition in unchanged form had lived through by the second half of the 20th century, when sport got itself into totally new social conditions determined with two world economical systems. The longstanding International Olympic Committee chairman Avery Brundage resisted pressure of the international sport associations and the national Olympic committees, his successor Lord Michael Killanin gave free play to it. Juan Antonio Samaranch who became unrestricted dictator of the Olympic movement in 80th and 90th of the 20th century opened gates with final validity. Just he provided for a payment of the high financial fees according to the socialistic model of the sport system. The XXIV. Olympic Games in Soul in 1988 were important in this because tennis players celebrated their come back on the Olympic stadiums after sixty-four years. Tennis was typical representative of the professional sport. What relation was between socialistic and capitalistic sport? Were athletes from the socialistic countries professionals? How the socialistic countries accepted changes into the Olympic movement in 80th of the 20th century? These and other questions keep one of keys for understanding contemporary situation in sport with his troubles: height of the athletes' fees, commercialisation, advertisement and promotion in the media, doping a fair play. I miss ethical and philosophical point of view on the professional sport problems. I continue my historical point of view in presented article. I want to show some lesser-known aspects of the professional sport and remind relations of the socialistic countries to the top sport during cold war. The thirst to succeed in the medal duel contributed to growth of the demands on sportsmen. The training took more and more time. That is why was increasingly impossible for sportsmen to have an occupation or studies. It proves that not only wealthy companies stood at the professional sport emancipation but also specific understanding of the sport amateurism in the socialistic countries policy.]